Late Neolithic Figurines as an Expression of Social Inequality - Jasna Vuković (Etnoantropološki Problemi, 2022)
Building upon the idea of Douglass Bailey (1994) that prehistoric figurines represent actual individuals, it is suggested here that their makers represented people in the manner they perceived them, following the role models familiar from their own society. This further implies that, on the grounds of certain indicators, it may be possible to identify social differences depending on the age, sex/gender, and possibly other modes of inequality. An attempt is made here to define the criteria identifying the markers – indicators of inequality, such as: representations of hair style and jewellery, size of figurines, as well as the correlation between these indicators and the details on the figurines’ bodies pointing to their sex/gender or age. In the assemblage from the site Pavlovac-Čukar, the correlation has been established between the representations ascribed as male and massive bangle bracelets and belts, indicating that adult male individuals of higher status were marked out by the number of bangles and the way of wearing the belt. A similar suggestion is proposed concerning the large-size figurines, marked with incisions perhaps representing tattoo marks, with looser breasts, indicating the possibility that older women obtained higher social status than the young ones. It is worth noting that in the case of the Vinča figurines little attention is paid to the representation of hair style, although it has been established that in the preindustrial societies, hair is an important indicator of social status, even more than jewellery. Hair length, specific hair styles, as well as various ornaments placed here, indicate sex/gender and social differences, various group and individual identities, as well as aesthetic ideas. Two heads from Čukar, as well as the one from Predionica, perform specific hair styles – hair shorter, reaching just below ears, and the crown is shaven. Bearing in mind that these figurines may show portrait characteristics, it may be suggested that these individuals may have achieved higher social status.